Estimation of pathways of the production of greenhouse gases in the tropical swamp forest in Thailand by stable isotope investigation - Narin Boontanon (2018)
Dynamics of greenhouse gases (N2O and CH4) with the dry-wet cycle along with the variation of oxidation-reduction boundaries were investigated in the tropical wetland in monsoon Asia. It was clarified that the production of N2O and CH4was closely related to the development of a redox boundary in the Bang Nara River systems. An intermittent increase in N2O was observed at the beginning of the rainy season, when a large amount of easily decomposable organic matter was introduced into the river. After 10 days, when dissolved oxygen was consumed completely at the middle reaches, the emission of CH4became maximal due to the possible occurrence of denitrification. The distribution of stable isotope ratios in N2O clearly demonstrated that nitrification is the major process for its production. Furthermore, the production of N2O in this study area was found to vary in time and space with changes in the redox boundary along the water flow.